2005
DOI: 10.1590/s0004-282x2005000500007
|View full text |Cite
|
Sign up to set email alerts
|

Seizure occurrence in patients with chronic renal insufficiency in regular hemodialysis program

Abstract: Hemodialysis-associated seizure is a complication of hemodialysis. This report describes the occurrence of seizures in patients with end stage renal disease on dialysis therapy at the Nephrology Institute of Mogi das Cruzes, São Paulo State, Brazil. A retrospective medical history of 189 patients was reviewed to investigate the occurrence of convulsive seizures during dialytic program. Seven patients with history of seizures were selected but five of them were included in our study. Three patients presented ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…As these two chronic diseases are very common and have high rates of sudden death, we evaluated what would be the scenario if the same person had both conditions 13 . In order to do it, we investigated the relationship of seizure frequencies in people with end-stage renal disease (ESRD) under regular dialysis program 14 . Seven out of 189 ESRD cases had convulsive seizure during the dialytic program 14 , therefore it was evident that despite the belief that seizures were rare among ESRD individuals receiving dialysis, this was not the case.…”
Section: View and Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As these two chronic diseases are very common and have high rates of sudden death, we evaluated what would be the scenario if the same person had both conditions 13 . In order to do it, we investigated the relationship of seizure frequencies in people with end-stage renal disease (ESRD) under regular dialysis program 14 . Seven out of 189 ESRD cases had convulsive seizure during the dialytic program 14 , therefore it was evident that despite the belief that seizures were rare among ESRD individuals receiving dialysis, this was not the case.…”
Section: View and Reviewmentioning
confidence: 99%
“…In order to do it, we investigated the relationship of seizure frequencies in people with end-stage renal disease (ESRD) under regular dialysis program 14 . Seven out of 189 ESRD cases had convulsive seizure during the dialytic program 14 , therefore it was evident that despite the belief that seizures were rare among ESRD individuals receiving dialysis, this was not the case. Indeed, this suggested that a clinical convergence of neurologists and nephrologists in the context would be helpful [13][14][15] .…”
Section: View and Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective and mainly due lack of data in the world, our research group decided to investigate the possible relationship between seizure frequencies in patients with end-stage renal disease (ESRD) under regular dialysis program 4 . Briefly, from 189 ESRD patients, 7 had suffered some type of convulsive seizure during dialytic program 4 . At that time, we concluded that despite the occurrence of seizures is considered rare among ESRD individuals receiving dialysis, it should be apparent that a true convergence of clinical nephrology and neurology should always be part of this scenario 4 .…”
Section: Opinionmentioning
confidence: 99%
“…Thus, as these two chronic diseases are very common in the world and also a global public health problem, a new line of translational research would have great value in helping neurologists and nephrologists to investigate what would be the best strategy to be drawn if these two chronic diseases involve the same individual. From this perspective and mainly due lack of data in the world, our research group decided to investigate the possible relationship between seizure frequencies in patients with end-stage renal disease (ESRD) under regular dialysis program 4 . Briefly, from 189 ESRD patients, 7 had suffered some type of convulsive seizure during dialytic program 4 .…”
mentioning
confidence: 99%